Palliative brachytherapy and external beam radiotherapy for dysphagia from esophageal cancer: a nationwide survey in Japan. (24th February 2021) - Kawamoto, Terufumi; Nakamura, Naoki; Saito, Tetsuo; Tonari, Ayako; Wada, Hitoshi; Harada, Hideyuki; Kubota, Hikaru; Nagakura, Hisayasu; Heianna, Joichi; Miyazawa, Kazunari; Yamada, Kazunari; Tago, Masao; et al.
Abstract: Background: International guidelines recommend brachytherapy for patients with dysphagia from esophageal cancer, whereas brachytherapy is infrequently used to palliate dysphagia in some countries. To clarify the availability of palliative treatment for dysphagia from esophageal cancer and explain why brachytherapy is not routinely performed are unknown, this study investigated the use of brachytherapy and external beam radiotherapy for dysphagia from esophageal cancer. Methods: Japanese Radiation Oncology Study Group members completed a survey and selected the treatment that they would recommend for hypothetical cases of dysphagia from esophageal cancer. Results: Of the 136 invited facilities, 61 completed the survey (44.9%). Four (6.6%) facilities performed brachytherapy of the esophagus, whereas brachytherapy represented the first-line treatment at three (4.9%) facilities. Conversely, external beam radiotherapy alone and chemoradiotherapy were first-line treatments at 61 and 58 (95.1%) facilities, respectively. In facilities that performed brachytherapy, the main reason why brachytherapy of the esophagus was not performed was high invasiveness (30.2%). Definitive-dose chemoradiotherapy with (≥50 Gy) tended to be used in patients with expected long-term survival. Conclusions: Few facilities routinely considered brachytherapy for the treatment of dysphagia from esophageal cancer in Japan. Conversely, most facilities routinely considered external beam radiotherapy. In the future, it will be necessary to optimize external beam radiotherapy. Abstract : Few facilities routinely considered brachytherapy for treating dysphagia from esophageal cancer in Japan. By contrast, most facilities routinely considered external beam radiotherapy.